Relationship among phenotypic and quality traits in indigenous and exotic accessions of linseed - Siddiqui, Ameena; Shukla, Sudhir; Rastogi, Anu; Bhargava, Atul; Niranjan, Abhishek; Lehri, Alok (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the relationship among phenotypic and quality traits in a set of indigenous and exotic accessions of linseed (Linum usitatissimum). The experimental material consisted of 151 accessions of linseed belonging to landraces and cultivars collected from diverse agroecological zones. Five randomly chosen plants of each accession in each replicate were tagged, and data were recorded for the 12 following agronomic traits: days to flowering, days to maturity, plant weight, plant height, tillers per plant, secondary branches per plant, capsules per plant, seeds per capsule, 1,000 seed weight, harvest index, seed yield per plant, and oil content. Capsules per plant, harvest index, and plant weight played a direct and indirect major role on seed yield. High heritability, coupled with high genetic advance for plant weight, secondary branches per plant, capsules per plant, and seed yield per plant, suggests that selection based on these traits can be effective. Regarding per se performance, the following accessions can be exploited for commercial cultivation: Shweta (5.41 g), Gaurav (5.07 g), and EX-3-3 (4.77 g) for seed yield; and Shubhra (45.09%), Mukta (44.94%), Laxmi-27 (45.06%), and Shweta (44.25%) for oil content. The chemical profiling of fatty acids obtained in the present study can provide a platform for the selection of accessions for the genetic improvement of linseed.